2004
DOI: 10.1016/j.febslet.2004.03.124
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of radioligand binding to a transmembrane receptor reconstituted into Lipobeads

Abstract: Lipobeads are hydrogel beads surrounded by a lipid bilayer membrane and have been developed to act as a cell analogue. The FLAG-tagged M 2 muscarinic receptor was incorporated onto the surface of the Lipobead by incubating pre-Lipobeads with proteoliposomes containing the receptor. Receptors reconstituted onto the surface of the Lipobeads were functional in that they bound the antagonists quinuclidinylbenzilate and scopolamine with characteristic muscarinic affinities. This demonstrates the feasibility of usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Liposomes were first reported for drug delivery in 1965 72. Liposome‐based templates include lipospheres and lipobeads 73–78. Liposome probes comprise an outer phospholipid layer forming a spherical vesicle that has an aqueous core, while lipobeads possess an inner polymeric core (see Figure 3 for examples of liposomes, lipobeads, and other non‐protein‐based DDS that have previously been developed).…”
Section: Liposome‐based Nanomedicine Platformmentioning
confidence: 99%
“…Liposomes were first reported for drug delivery in 1965 72. Liposome‐based templates include lipospheres and lipobeads 73–78. Liposome probes comprise an outer phospholipid layer forming a spherical vesicle that has an aqueous core, while lipobeads possess an inner polymeric core (see Figure 3 for examples of liposomes, lipobeads, and other non‐protein‐based DDS that have previously been developed).…”
Section: Liposome‐based Nanomedicine Platformmentioning
confidence: 99%
“…Our Lipobead membrane lipid composition was 48% ePC, 48% PS, and 4% cholesterol. This composition was selected in anticipation of experiments with transmembrane receptor constituted proteoliposomes (see Park et al, 2004). Thus, the high fraction of phosphatidylserine used here may have further restricted probe diffusivity.…”
Section: Figurementioning
confidence: 99%
“…With the latter two methods, the lipobeads of 1-μm diameter are produced [2,7,23,25,28,31]. To prepare giant lipobeads with a diameter up to 100 μm, the inverse suspension polymerization (ISP) method is commonly applied [6,24,35,[43][44][45].…”
Section: Hydrogel/liposome Mixingmentioning
confidence: 99%
“…The first proteo-lipobeads were prepared when transmembrane receptors were reconstituted into the lipid bilayer of lipobeads [45]. It was found that the receptors retained their nativespecific binding.…”
Section: Proteins Within Lipid Bilayermentioning
confidence: 99%
See 1 more Smart Citation